Alright, lets say the measure of the 3rd angle (the smallest one) is x degree, then measure of the 1st angle will be (x + 25) degree, and 2nd one: 3x degree. The sum of all the angles in any triangles is 180 degrees.
(x + 25) + 3x + x = 180
5x + 25 = 180 ---> 5x = 180 - 25 ---> 5x = 155 ---> x = 155/5 ---> x = 31o (third angle)
31 + 25 = 56o (first angle)
3 × 31 = 93o (second angle)
56 + 93 + 31 = 180
Answer:
9.52
Step-by-step explanation:
Answer:
(2x² + 5x + 2) = (2x + 1)(x +2)
Step-by-step explanation:
Given expression is (2x² + 5x + 2).
We have to factorize the given expression.
(2x²+ 5x + 2) = 2x² + 4x + x + 2
= 2x(x + 2) + 1(x + 2)
= (2x + 1)(x + 2)
So the factored form of the given expression will be (2x + 1)(x + 2).
Answer:
46°
Step-by-step explanation: